Memahami Penderitan Orang Kristen Menurut Kitab 1 Petrus 4 : 12-19 - Ariance Lende; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
There are believers who believe that suffering as a Christian is a curse that God does not want. This suffering is the only way to experience the glory of Christ. In this case, the author believes that this view is not entirely correct. The letter of 1 Peter has a lot to say about the suffering of believers. This suffering is the only way to experience the glory of Christ. In this case, the author believes that both views are not completely correct. The letter of 1 Peter has a lot to say about the suffering of believers. The reality of suffering experienced by society mainly occurs as a result of criminal acts that contain elements of injustice, disease, accidents, violence, rape, etc